Práticas de combate ao analfabetismo no Ceará - Lima, João Henrique Brito (2019)
This text aims to identify the conceptions of literacy in the vision of the policies developed to combat illiteracy between the conflicts interests of the rulers and the non-literate population at the beginning of the First Republic. Brazil has a large territorial extension, with wide social inequality and a high poverty rate. This significantly affects the fight against illiteracy and its eradication in many ways.